2014
DOI: 10.3892/ol.2014.2379
|View full text |Cite
|
Sign up to set email alerts
|

Immune reconstitution from peripheral blood mononuclear cells inhibits lung carcinoma growth in NOD/SCID mice

Abstract: Drug resistance and immune deficiency are important factors for the poor prognosis of lung carcinoma. The present study explored the possible protective effect of immune reconstitution from peripheral blood mononuclear cells (PBMCs) on multi-drug-resistant human lung carcinoma Am1010 cells in non-obese diabetic/severe combined immunodeficient (NOD/SCID) mice. The inoculated tumor fragments grew rapidly in the NOD/SCID mice. The growth was significantly inhibited by intraperitoneal injection of PBMCs. In the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…These factors, as well as the immunodeficiency status of the PDX models, may contribute to the higher CTC/DTC detection rates we find in PDX models. In future, it will be of interest to compare CTCs/DTCs from patients side-by-side with those derived from matched PDXs as well as to compare characteristics of CTCs/DTCs within various immunodeficiency models and versus those with reconstituted immune components [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…These factors, as well as the immunodeficiency status of the PDX models, may contribute to the higher CTC/DTC detection rates we find in PDX models. In future, it will be of interest to compare CTCs/DTCs from patients side-by-side with those derived from matched PDXs as well as to compare characteristics of CTCs/DTCs within various immunodeficiency models and versus those with reconstituted immune components [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…to bladder cancer. However, similar to some of the related studies [6,[14][15][16], this study did not include any T cell functions comparison between the humanized control group and the model group. Yet, we strongly believe that it would be of great significance to our future studies to explore the possibility of interaction between the immune system and the tumors using this model.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Sabzevari H et al [43] demonstrated that when engrafted with T lymphocytes, SCID mice bearing tumors showed a significant reduction of metastasis in the number of foci and in the lymph nodes. Liu et al [6] found the xenograft growth in SCID mice was significantly inhibited by intraperitoneal injection of PBMCs. So they concluded that "PBMC transplantation inhibits lung carcinoma progression via the reconstitution of the immune system, particularly of cytotoxic T lymphocytes.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Previous studies have demonstrated that reconstitution of the immune system by transplanting human PBMC hampers tumor growth in immunocompromised mice [27,28]. In this study, tumor volume was measured every alternate day, from day 4 after tumor inoculation.…”
Section: Taso Administration Accelerates Tumor Rejection In Hupbl Nsg Micementioning
confidence: 97%